(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2026)
As user expectations for comfort and product quality increase, reducing noise from household appliances like hair dryers has become increasingly important. This study investigates the effectiveness of a perforated sound absorber in reducing noise emitted by a 2100W commercial hair dryer. The initial acoustic characterization was performed by measuring the overall sound power level (SWL) using a hemispherical microphone array, in accordance with ISO 3742. To identify the dominant noise source, Microflown Scan & Paint technology was employed, revealing the air inlet as the primary noise source. A perforated sound absorber was designed to be mounted at this location. Key design parameters–perforation diameter, panel thickness, perforation ratio, and air cavity depth–were optimized using sound absorption coefficient (SAC) simulations. The simulation model was validated through experimental measurements using a standard two-microphone impedance tube setup in accordance with ASTM E1050-98. The optimized design was fabricated via fused deposition modeling (FDM) using PLA and installed at the air inlet of the hair dryer. Subsequent SWL measurements indicated a noise reduction of 2.15 dB(A) compared to the hair dryer without the attachment, confirming the absorber’s potential for targeted noise control.